An Alexandrov topology for maximal Cohen-Macaulay modules - Akdenizli, M.; Aytekin, B.; Çetin, B.; Esentepe, O. (Elsevier B.V., 2024)
Using the theory of cohomology annihilators, we define a family of topologies on the set of isomorphism classes of maximal Cohen-Macaulay modules over a Gorenstein ring. We study compactness of these topologies. © 2023 The Author(s)
Keywords: Alexandrov Topology; Cohomology Annihilators; Maximal Cohen-Macaulay Modules